BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PENGAMBILAN KEPUTUSAN UNTUK BER-KB PADA KELOMPOK IBU DIWILAYAH PUSKESMAS I SUKOHARJO - Sri Nuryani; Faizah Bety Rahayuningsh (Jurnal Berita Ilmu Keperawatan, 2009)
The election a method, besides considering effectivity, side effects, advantage and limitations that is is sticking at one particular contraception method, also there are individual factors of acceptor candidate and also factor eksternal which in the end influences decision making of the acceptor candidate (Erfand, 2008). Purpose of this research is some culture factors relating to decision making in family to plan at group of mother is region of Puskesmas I Sukoharjo. This research done by using method descriptive correlative. Research is executed in Wilayah Puskesmas I Sukoharjo. Population from this research is fertility age woman that is is not applies KB and using natural KB in Wilayah Puskesmas I Sukoharjo. Sample 96 up to standard has responders of inklusi and ekslusi. Examination of data analysis applies test Regresi Logistik. This research concludes: (1) level of cultural and religion trust at group of mother in region Puskesmas I Sukoharjo strong mean, that is with percentage of 61%, (2) level of education at group of mother in region Puskesmas I Sukoharjo low mean where mostly they don't go to school, SD/MI and SMP/MTs where percentage of entirely is 64%, (3) election of decision in family plans at group of mother in region Puskesmas I Sukoharjo most of natural KB, that is with percentage of 69%, (4) there is relationship signifikan level of cultural and religion trust to decision making in family plans at group of mother in region Puskesmas I Sukoharjo, and ( 5) there is relationship signifikan level of education to decision making in family plans at group of mother in region Puskesmas I Sukoharjo